Catalyst‐Transfer Suzuki–Miyaura Condensation Polymerization of Stilbene Monomer: Different Polymerization Behavior Depending on Halide and Aryl Group of ArPd(tBu3P)X Initiator. Issue 3 (7th August 2018) - Nojima, Masataka; Kamigawara, Takeru; Ohta, Yoshihiro; Yokozawa, Tsutomu
ABSTRACT: We report Suzuki–Miyaura coupling polymerization of tetraalkoxy‐substituted 4‐bromostilbene‐4′‐boronic acid1 with several t ‐Bu3 P‐ligated Pd initiators; this is the first example of catalyst‐transfer condensation polymerization (CTCP) of a monomer containing a carbon–carbon double bond. When o ‐tolylPd( t Bu3 P)Br was used as the initiator, the o ‐tolyl group was not introduced at the polymer end, but polymer with boronic acid at one end and bromine at the other was obtained. However, when we employed stilbenePd( t Bu3 P)I generated in situ from iodostilbene and Pd( t Bu3 P)G2 precatalyst, or isolated ArPd( t Bu3 P)X (Ar, X = Ph, I; o ‐tolyl, I; and Ph, Br), the aryl group was introduced at the polymer end, indicating that CTCP of1 proceeded. Therefore, the iodide and aryl group of the Pd initiator complex is crucial for CTCP of1 . However, the molecular weight distribution of the obtained polymer was broad, possibly because coordination of the carbon–carbon double bond of1 to ArPd( t Bu3 P)I resulted in slow initiation. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 297–304 Abstract : Suzuki–Miyaura coupling polymerization of1 with o ‐tolylPd( t Bu3 P)Br affords poly(biphenylenevinylene) (PBPV) with B(OH)2 /Br ends, whereas polymerization with ArPd( t Bu3 P)I yields PBPV with Ar/Br ends and shows chain‐growth polymerization character.